Pembebanan Jaminan Fidusia Dan Akibat Hukumnya - Sahruddin - (Jatiswara, 2011)
In mantaining the sustanablity of the developement, the actors of the developement either private person or legal entity need huge funds. To fulfill this need, it reqiures the existance of a monetery institue, either a banking or non-banking institute, which could provides capital loans or fundings on fiduciary mortgage loan. Fiduciary mortgage loan is frequently being used by debtors becouse this kind of mortgage loan comes with a lot of advantages. One of those is that the object of fiduciary mortgage loan is not required to be delivered and held by creditor, so that debtor could still make use it to runs his/her business. Problem formulation of this research as follows: how to burden a thing with fiduciary mortgage loan under the Fiduciary Mortgage Law 2). Is there any legal certainty in burdening a thing with fiduciary mortgage loan?. This research is aiming to find out how to burden a thing with fiduciary mortgage loan under the Fiduciary Mortgage Law, and whether there is any legal certainty in burdening a thing with fiduciary mortgage loan. This research used a juridical normative approach. It uses qualitative data obtained through library research. Data collecting in this research is carried out through documentary research. To analyze the data in this research, it uses descriptive-qualitative analysis. The research results reveal that the process of burdening a thing with fiduciary mortgage loan is carried out through two phases which are consist of burdening phase and registration phase. Burdenig phase is carried out through notarial deed. As for registration phase is carried out at the office of the fiduciary mortgage registration in the judicial departement office. The legal certainty form of notarial deed of burdening a thing with fiduciary mortgage loan is not only reflected through notarial deed but also the emergency of preferen right for the fiduciary mortgage holder (creditor) and the object of fiduciary mortgage loan is easy to execute.